Analysis of Market Reactions Before And After the Announcement of the Covid 19 Virus Pandemic - Ni Luh Putu Mita MIATI; I Gde Agung Wira PERTAMA (International Journal of Environmental, Sustainability, and Social Science, 2020)
this study will test the market reaction seen from the JCI on the announcement of the Covid 19 Virus Pandemic on the Indonesia Stock Exchange. This study uses secondary data, namely composite stock price index from companies listed on the Indonesia Stock Exchange (IDX) in 2020. This study uses an event study to analyze the movements that occur in the JCI from day to day with an event period of 10 days. The population used in this study was composite stock price index data on the 5 days before the announcement and 5 days after the announcement. The data analysis technique used to test the hypothesis in this study was the statistical analysis of Paired Sample T-test. This test tool is part of the comparative hypothesis test or comparison test. From the results it can be concluded 1) There is a difference in composite stock price index data before and after the announcement of the COVID-19 pandemic on 12 March 2020, 2) The announcement of the COVID-19 pandemic has an effect on the differences in the JCI before the announcement and after the announcement of the COVID-19 Pandemic.